Reproductive Development of Male Rats Exposed In Utero to Stress and/or Sertraline - Quiarato Lozano, Ana Flávia [UNESP]; Marques Tavares, Bruna [UNESP]; Villela E Silva, Patrícia [UNESP]; Franco De Barros, Jorge Willian [UNESP]; De Grava Kempinas, Wilma [UNESP] (Oxford University Press (OUP), 2022)
Despite increased prescription of sertraline during pregnancy, little is known about its action on reproductive development. Therefore, this study aimed to investigate the impact that stress, associated or not with sertraline, causes on the reproductive development of male rats. Pregnant Wistar rats were divided into 4 groups (n = 16/group): CO - received filtered water; SE - received 20 mg/kg sertraline; ST - submitted to restraint stress and received filtered water; SS - submitted to restraint stress and received sertraline. The treatment was carried out from gestational days (GDs) 13-20. The animals were euthanized on GD 20 (n = 8/group), postnatal day (PND) 45 (n = 8/group), and PND 110 (n = 8/group). The testes and epididymis were analyzed histologically, and immunohistochemistry was performed on the testes by proliferating cell nuclear antigen (PCNA) and the Wilms tumor protein (Wt1). Sperm quality was also analyzed on PND 110. The evolution of body weight, anogenital distance (AGD), and puberty installation day were also verified. Statistical analysis: 2-way ANOVA or Kruskal-Wallis test (p ≤. 05). Fetal testes presented a large number of acidophilic cells in the sertraline-exposed groups. The SS group also showed a decrease in the nuclear volume of Leydig cells. This same group showed low expression of PCNA and Wt1, decreased weight of the testes and epididymis, lower AGD, and delayed puberty installation. The adulthood groups exposed to sertraline presented alterations in sperm morphology and motility. The results demonstrated that prenatal exposure to sertraline compromises the development of the rat reproductive system.
Keywords: gestational stress; male rats; reproductive system; sertraline